LOGIKA FUZZY UNTUK MENENTUKAN MINAT WISATA MASYARAKAT DI KOTA BATAM - Alvendo Wahyu Aranski; Franky Chia (IIB Darmajaya, 2018)
Batam is a city with millions of tourism potential in the future. With its geographical location is very strategic, the city of Batam should be a tourist destination for all people, especially the people of Batam city itself. However, the lack of tourist interest for the community in Batam City caused several factors such as distance to the location of the tour, the facilities provided, and entrance fees to the tourist attractions. By using Mamdani method on Fuzzy logic, determination of tourism interest for Batam city community can be done. With a value of 43 on the results of matlab calculation, stated that the interest of community tourism in the city of Batam is in the fuzzy set quite interested.Keywords—Mamdani, Fuzzy, Tourismn